Exploring brain mechanisms underlying Gulf War Illness with group ICA based analysis of fMRI resting state networks. (14th May 2019) - Gopinath, Kaundinya S.; Sakoglu, Unal; Crosson, Bruce A.; Haley, Robert W.
Highlights: FC between motor, somatosensory, visual and auditory networks are impaired in GWI. Language networks' FCs to motor and sensory networks are impaired in GWI. FC impairments in GWI are consistent with its neurological symptoms. Abstract: Around 200, 000 veterans (up to 32% of those deployed) of the 1991 Gulf War (GW) suffer from GW illness (GWI), which is characterized by multiple deficits in cognitive, affective, sensory and nociception domains. In this study we employed resting state fMRI (rsfMRI) to map impairments in brain function in GWI with advanced network analysis. RsfMRI data was obtained from 60 GWI veterans and 30 age-matched military controls. Group independent component analysis (GICA) was conducted to probe the functional connectivity networks in all 90 subjects. GICA revealed impaired functional connectivity (FC) in GWI veterans between a number of brain function networks consistent with their self-reported symptoms. GWI veterans exhibited impaired FC between language networks, and sensory input networks of all modalities as well as motor output networks. GWI veterans also exhibited impaired FC between different sensory perception and motor networks, and between different networks in the sensorimotor domain. These FC impairments provide putative mechanism of central nervous system dysfunction in GWI.